Analysing buildings from context to detail in time : ABCD research method - Zijlstra, Hielkje (IOS Press, 2009)
Uses technology to develop a more comprehensive research method to assess buildings. In this book the focus is on construction engineering, the study of the requirements associated with constructing buildings.